An Insight Into Structural Design Against Deflection. (August 2018) - Ji, Tianjian; Cunningham, Lee S.
Abstract: There are "rules of thumb" for designing structural elements such as beams, columns and floors, which are simple and effective. Such rules are familiar to most engineers and are widely used to develop quick preliminary designs. Are there similar types of "rules of thumb" that can be used for conceptual designs to achieve smaller deformations of whole structures or make such structures more effective, efficient and elegant? This article demonstrates four conceptual solutions to reduce deflections of structures which are all related to internal forces. Examples are provided to illustrate the use and effectiveness of the concepts, including some well-known structures.